An analysis of valence electronic structure from a viewpoint of resonance theory: Tautomerization of formamide and diazadiboretidine. Issue 23 (10th June 2021) - Nakatani, Kaho; Higashi, Masahiro; Fukuda, Ryoichi; Sato, Hirofumi
Abstract: The resonance theory is still very useful in understanding the valence electron structure. However, such a viewpoint is not usually obtained by general‐purpose quantum chemical calculations, instead requires rather special treatment such as valence bond methods. In this study, we propose a method based on second quantization to analyze the results obtained by general‐purpose quantum chemical calculations from the local point of view of electronic structure and analyze diazadiboretidine and the tautomerization of formamide. This method requires only the "PS "‐matrix, consisting of the density matrix (P‐matrix) and overlap matrix, and can be computed with a comparable load to that of Mulliken population analysis. A key feature of the method is that, unlike other methods proposed so far, it makes direct use of the results of general‐purpose quantum chemical calculations. Abstract : A simple methodology for extracting the resonance structure embedded in a molecular orbital (MO) wave function was studied. The analysis requires "PS "‐matrix, density and overlap matrix only, and is easy to use. A variety of molecular systems were examined, including formamide and diazadiboretidine isomers, to demonstrate its usefulness.